2013
DOI: 10.3233/cbm-130345
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of brain-derived neurotrophic factor (BDNF) are decreased in colorectal cancer patients

Abstract: The serum levels of BDNF were significantly lower in colorectal cancer patients when compared to a control population, and this did not differ between different Dukes' stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
2
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
3
17
2
4
Order By: Relevance
“…Although no association with the CRC stage was detected, which was in accordance with a previous study (16), a significant increase of these rates (P=0.0059 for BDNF and P=0.0457 for NT4/5) was observed in patients who were under psychotropic treatments, in particular for BDNF in patients treated with benzodiazepine (P= 0.0221). As benzodiazepine is able to act on the central nervous system, it is expected to affect the levels of BDNF, as previously demonstrated in patients treated for depression with diazepam (5 mg), or tandospirone (20 mg) or paroxetine (10 mg), versus matched placebo (8).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although no association with the CRC stage was detected, which was in accordance with a previous study (16), a significant increase of these rates (P=0.0059 for BDNF and P=0.0457 for NT4/5) was observed in patients who were under psychotropic treatments, in particular for BDNF in patients treated with benzodiazepine (P= 0.0221). As benzodiazepine is able to act on the central nervous system, it is expected to affect the levels of BDNF, as previously demonstrated in patients treated for depression with diazepam (5 mg), or tandospirone (20 mg) or paroxetine (10 mg), versus matched placebo (8).…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, only one study has assessed BDNF in the serum of CRC patients, revealing that it was decreased in patients compared with that in controls and was not associated with the stage of CRC (16). Among other studies, BDNF expression shows a large variation in different cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found BDNF/TrkB are up-regulated in countless types of cancers, such as breast cancer, carcinoid, cervical, colorectal, glioma, liver, lung (6)(7)(8)(9)(10)(11)(12). Some studies even revealed BDNF might be an important prognostic factor for cancers (12,(48)(49)(50). Recently, BDNF/TrkB pathway has been demonstrated to transactivate EGFR, a growth factor receptor commonly up-regulated in many cancers (43,51).…”
Section: Oncogenic Role Of Bdnf In Tumormentioning
confidence: 99%
“…Przedmiotem wielu badań ostatnich lat jest udział BDNF i jego receptora TrkB w onkogenezie. Po raz pierwszy został on scharakteryzowany w przypadku nowotworów dotyczących ośrodkowego układu nerwowego (OUN), jednak w ostatnich latach wykazano, że związek ten odgrywa także kluczową rolę w patogenezie nowotworów nieneurogennych, w tym raka jelita grubego [5]. extracellular signal regulated kinase (ERK) and serine/threonine protein kinase (Akt) activated by BDNF additionally cause the resistance of cancer cells to cytostatic drugs [6,7,8].…”
Section: Wstępunclassified
“…The participation of BDNF and its TrkB receptor in oncogenesis has been the subject of many studies in recent years. It was first characterised in the case of neoplasms affecting the central nervous system (CNS), but in recent years it has been demonstrated that this compound also plays a key role in the pathogenesis of non-neurogenic neoplasms, including colorectal cancer [5]. The signalling pathways of, e.g.…”
Section: Introductionmentioning
confidence: 99%